Dissidence policies: i international meeting linguistic rights as human rights in Latin America - De Mauro, Sofía; Bixio, Beatriz (Heterotopías, 2019)
The last week of March was powerful in Córdoba. He had his preliminaries in the march of 8M and the Day of Remembrance: there were two more marches, there were multitudinous meetings that called us to demand justice, to interpellate memory, history, our societies and the political-economic conjuncture. And, when there was still the memory of those two contestatory actions, days later, on March 27, we received for the first time in Cordoba the King of Spain, Carlos Borbón, and the president of the nation, Mauricio Macri, for the opening of a magno event: the VIII International Congress of the Spanish Language, possibly the most important official event of the last decades in Córdoba.In clear dissent, and almost in a mirror -the reverse image-, the First International Meeting took place: linguistic rights as human rights in Latin America, organized by the Faculty of Philosophy and Humanities of the National University of Córdoba. Once again, the pendulum submission-disobedience that marks the history of Cordoba showed the fragmentation of the senses on the social world.